Effect of long term treatment with oxitropium bromide on airway secretion in chronic bronchitis and diffuse panbronchiolitis. - Tamaoki, J. (1994)
BACKGROUND--Anticholinergic bronchodilator drugs improve lung function in chronic bronchitis but less is known of their effects on the volume and physical properties of sputum in conditions associated with excessive airway secretions. This study examines the effects of the regular use of oxitropium bromide in such patients. METHODS--The study was conducted in a parallel, double blind, placebo controlled fashion. Patients were divided into two groups: the first group (n = 17) received oxitropium bromide from a metered dose inhaler (two puffs three times daily; 100 micrograms/puff) for eight weeks, and the second group (n = 16) received placebo. Lung function was measured as forced expiratory volume in one second (FEV1) and vital capacity. In evaluating airway secretion, daily amount of expectorated sputum, percentage solid composition, viscoelastic properties including elastic modulus and dynamic viscosity, and sputum microbiology were determined. RESULTS--Oxitropium bromide increased FEV1 and decreased the mean (SE) sputum production from 61(4) to 42(3) g/day after treatment, whereas placebo had no effect. Bacterial density and sputum flora were unchanged, but solid composition and elastic modulus increased from 2.52(0.43)% to 3.12(0.34)%, and 68(12) dyne/cm2, respectively, in the group taking oxitropium bromide. CONCLUSIONS--Regular treatment with oxitropium bromide not only improves airflow limitation but also reduces sputum production, probably through the inhibition of both mucus secretion and water transport, the latter component being predominant.